Battery charger load-following controller for over-voltage and under-voltage conditions - Shahid, Arqum; Manzoor, Sajjad; Khan, Uzair; Majeed, Afraz Hussain; Khan, Ilyas; Mohamed, Abdullah (Frontiers in Energy Research, 2023)
Battery charging systems are integral to the efficient operation and economic benefit of various applications, from electric vehicles to renewable energy storage. However, maintaining battery charging according to specifications during voltage variations, including short or prolonged under-voltage and over-voltage conditions, presents a significant challenge. These voltage variations can impact the thermal safety and charging time of batteries, potentially affecting their overall performance and life span. In order to address these challenges, this paper proposes a smart charging control method designed to control both the battery charging voltage and load voltages. This method is equipped to handle utility interruptions by using regulated AC–DC converters, while an automatic interconnected DC regulator controls the battery state of charge (SOC) and load supply. This dual control mechanism ensures efficient performance under various conditions. Extensive simulations validate the effectiveness of the proposed method, demonstrating its ability to maintain a constant voltage supplied to the load and ensures the thermal safety of the system during under- and over-voltage conditions. Additionally, an analysis of the thermal effect of the charger under these voltage conditions provides valuable insights into the thermal performance of the system, which is a critical aspect of battery charging systems. The proposed charging control method offers a comprehensive solution for efficient battery charging under various voltage conditions, thus contributing to the better performance, thermal safety, and longevity of batteries.